Structure and Bioactivities of a Novel Polysaccharide Extracted From Dendrobium huoshanense by Subcritical Water - Wang, Li; Mao, Yi-gui; Zeng, Xiang; Liu, Na; Niu, Chao-fei; Li, Xin-xin; Ma, Bing-ji; Guo, Lan-ping; Yang, Xiao-long (Frontiers in Nutrition, 2022)
In this study, the polysaccharide was extracted by subcritical water from Dendrobium huoshanense. A novel polysaccharide (DHPs-1) was obtained through several purification steps and its structure and bioactivity were investigated. Structural analysis indicated that the weight-average molecular weight of DHPs-1 was 5.0 × 104 Da and it was mainly composed of glucose (65.04%), mannose (14.23%), galactose (8.17%), galacturonic acid (6.41%), rhamnose (2.34%), and xylose (1.25%). 1,4-Glcp, and 1,4,6-Galp were existed in the backbone of DHPs-1. The residues of 1,3,4-Galp, 1,4-Manp, 1,4-Galp, and 1,3,4,6-Galp could be in the backbone or the side chains with the non-reducing terminal of α-Manp. Bioactivity tests indicated that DHPs-1 had immunomodulatory activity in that it significantly enhanced transcript levels of cytokines [Tumor necrosis factor-α (TNF-α), Interleukin-6 (IL-6), Interleukin-1β (IL-1β), and Interleukin-10 (IL-10)]. DPPH and hydroxyl radical scavenging tests showed that it had good antioxidant activity. These results reveal that DHPs-1 could be developed as a safe immunomodulatory agent and antioxidant for pharmacological or functional food applications.